QTL Mapping of Yield, Yield Components, and Morphological Traits in Rice (Oryza sativa L.) Using SSR Marker - Untung Susanto; Hajrial Aswidinnoor; Jajah Koswara; Asep Setiawan; Vitaliano Lopena; Lina Torizo; Virk S. Parminder (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
The experiment was aimed at identifying QTL (quantitative trait loci) controlling ten traits of yield, yield component and plant morphology of rice based on BC1F1 of IR75862-206-2-8-3-B-B-B//IR64 mapping population consisted of 115 plants. It was arranged in Completely Randomized Design with three replicates. Ninety three SSR markers spread across the twelve rice chromosomes were used to map the QTL. These markers were mostly segregated according to Mendel Law except for fourteen markers. There were eleven QTL detected in eight traits, i.e., heading date, flag leaf length, plant height, panicle length, panicle weight, seed set, weight of 100 grains, and grain weight per plant, meaning that one or two QTL were detected in each trait. These QTL were located at chromosome 2, 3, 4, 6, 11, and 12. Some QTL were located at the same chromosome even at the same location indicating the close association of the traits. It also indicated that there were common QTL which were found across genetic background and specific QTL which were found at specific genetic background. Further study was prospective for the molecular marker application in rice improvement. Key words: QTL, agronomic traits, SSR, rice